Effects of online teaching and learning on mental health of students, teachers and parents: Case study in an international school / Kanaheswaree Rajendran - Kanaheswaree, Rajendran (2022)
There has been a rapid disruption of the education system since the Covid Pandemic hit the world, affecting more than 200 nations. Learning institutions were closed indefinitely, leading to more than ninety-five per cent of students facing the impact. For this reason, there have been some changes in different spheres of life due to distance in movement, which came as a policy to control the spread of the virus. When re-opening the school came after a long period of staying at home, it came with many challenges because there were many standard rules. There is a feeling of dilemma, insecurity and uncertainty about learning at large. There have been different ways of learning introduced, one of them being online learning. Some factors have intervened in the experience, and many students and teachers have been affected. Prolonged lockdown and fatigue have brought mental health concerns for students, teachers, and parents. There has been a challenge of emotions from students' connection to their fellow students and teachers. Their academic results have been greatly affected due to this drastic unexpected change. This case study examines on determining the factors that causes mental health disturbance for teachers, students and parents while online teaching and learning process is being conducted during pandemic period. This study was conducted through survey and interview session. SPSS software was used to analyse the data from the survey question. Subsequently, this study is to identify the mitigation methods that can be implemented to eliminate or to reduce the occurrence of mental health in hope that online studies will be executed in the future as there is the hope of improvement in communication between the people involved. Thus, the introduction of digital learning will have its way which will improve the internet exploration.